Identifikasi Hubungan Antara Salinitas dan EC (Electrical Conductivity) Untuk Pengembangan Mitigasi Pengukuran Numerik-in Situ di Area Estuari: Mitigasi Kebencanaan Kualitas Air di Muara Kerandangan - Budianto, Arif; Alaydrus, Alfina Taurida; Rahayu, Susi; Andini, Mira; Anggriani, Ni Ketut; Fajarica, Shinta Desiyana (LPPM Universitas Mataram, 2025)
The dynamic nature of estuarine waters necessitates new and accurate methodological approaches for determining salt content or salinity. This can be achieved through direct and real-time measurement of instantaneous and daily EC (Electrical Conductivity) levels in estuaries using EC sensors. On the other hand, similar real-time research has been limited, especially for studies of a continuous real-time nature. Therefore, this study aims to identify the relationship between EC and salinity in an estuary, using the area around the Batulayar estuary, West Lombok Regency, as a case study, employing a direct measurement model continuously for one full day. Measurements were conducted over 5 days during different lunar phases, using direct data acquisition and a numerical linearity approach via data analysis plug-ins. The identification results demonstrate a relationship between EC and salinity. At minimum values, salinity decreases as EC decreases. This reduction follows a quadratic pattern, with an obtained coefficient of determination (R²) of 0.8684 (y = 87397x² – 11173x + 2004.8). This characteristic is also supported by other measured parameters, such as TDS (Total Dissolved Solids), which exhibits a linear relationship with EC. The relationship characteristic between TDS and EC is considerably stronger, as indicated by a linear equation (R² > 0.90).